Handbook of research on operational quality assurance in higher education for life-long learning - Nuninger, Walter, 1969-; Chatelet, Jean-Marie, 1951- (IGI Global, 2020)
"This book examines quality management and assurance programs and standards in college-level environments"
Keywords: vysokoškolské studium; normy a standardy; management jakosti; college study; standards; quality control; kolektivní monografie; případové studie; collective monographs; case studies